(untitled) (Journal of the College of Basic Education, 2022)
The Qur’anic miracle in the aesthetic philosophy of education shows the pedagogic aesthetic pedagogy of the child, following the foundations and pedagogical methods of preparing the generations, so its effective role in the civilization of society and its scientific and developmental progress must be fulfilled. The research aims to identify the Quranic miracle in the aesthetic philosophy of child rearing. It also includes a system of fields and principles of the aesthetic education philosophy of the child in the Arab-Islamic heritage through a number of Arab Muslim thinkers. The research also deals with the child in the light of the philosophical vision of aesthetic aesthetic education, including the idealistic philosophy - realism - pragmatism. The relationship between the child and religion - the child and humanity - the child and the intellect - also includes conclusions which mean faith in the conscious assimilation of technology (technology) and the acquisition of skills in dealing